CONTRIBUTION OF PEOPLE'S ARTIST OF UZBEKISTAN GAVHAR MATYOKUBOVA TO KHOREZM DANCE SCHOOL (Archive of Conferences, 2021)
People's Artist Gavhar Matyokubova's Khorezm dance school and its stages of development are mentioned. Extensive use of modern and advanced teaching methods in this academy, comprehensive development of students' talents. It is scientifically revealed that our national cultural heritage and dance have existed since time immemorial.